Pengaruh Kuat Arus Dan Variasi Sudut Kampuh Pengelasan SMAW Pada Sambungan Pelat Baja AISI E 2512 Terhadap Ketangguhan Serta Uji Anova - Suwarto; Tato, Markus; Mangando, Mangando; Tandilittin, Harsman (Indonesian Society of Applied Science, 2024)
Welding is a process of joining two metals where the metals become one due to heat with or without pressure. In this research, the welding process was carried out using a SMAW (Shield Metal Arc Welding) welding machine or electric arc welding using wrapped electrodes to determine the effect of seam type and current on toughness as well as an anova test. The base metal used is AISI E 2512 steel. The welding variables chosen are seam angles 600, 700, and 800, while the current variables used are 100A, 90A and 80A, then impact testing and anova tests are carried out. From the research results obtained. The highest impact strength is at a seam angle of 800 and a current of 100A, namely 1,802 joules/mm2, for the 700 seam angle group, the highest tensile strength value is 1,793 joules/mm2, while the lowest value is at a seam angle of 600, a current of 80A is 1,717 joules/mm2 and at Anova test shows that the mechanical properties of the weld will depend on the shape of the weld and the current chosen, so the seam angle and current strength have a significant influence on the impact strength or toughness of the steel..